Accountability and Transparency as the Implementation of Financial Accounting Standards Interpretation (ISAK) 35 (Study on Non-Profit Entities) - Vista Yulianti; Dian Sulistyorini Wulandari; Marina (East Asian Journal of Multidisciplinary Research, 2023)
This study aims to determine the reasons for the revocation of PSAK No. 45 and the application of ISAK 35 and to analyze the presentation of the financial statements of the Yayasan Bina Integrasi Edukasi on the Presentation of the Financial Statements of Non-Profit-Oriented Entities. This type of research is qualitative through a case study approach. The research method used in this research is descriptiveThe results of this study indicate that the reasons for the revocation of PSAK No. 45 are that it has been regulated by another SAK. Then, the Yayasan Bina Integrasi Edukasi presented its financial statements based on ISAK 35. Then, there are not many differences regarding the presentation of PSAK No. 45 and ISAK No. 35 in the financial statements of non-profit organizations. Keywords: Interpretation of Financial Accounting Standards (ISAK) 35, Statement of Financial Accounting Standards (PSAK) No. 45, presentation of financial statements, foundations.